Role Green Logistics Mediation in Improving Green Supply Chain Performance through Sustainable Manufacturing and Reverse Logistics - Jonathan Wibisono; Timotius FCW Sutrisno (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the role of green logistics as a mediating variable in the relationship between sustainable manufacturing and reverse logistics on green supply chain performance in manufacturing companies in East Java. A quantitative approach was used through a questionnaire survey of manufacturing managers, with covariance-based Structural Equation Modeling analysis using AMOS. The measurement model was tested for validity and reliability, while the structural model was used to examine the direct and indirect influences between variables. The results show that sustainable manufacturing has a significant impact on green logistics, and green logistics has a significant positive impact on green supply chain performance. Conversely, reverse logistics has no significant impact on either green logistics or green supply chain performance, so its contribution to green supply chain performance is still limited. These findings indicate that improving green supply chain performance is more effectively achieved through the integration of sustainable manufacturing practices with green logistics rather than relying solely on reverse logistics, which is still partial and reactive. This study positions green logistics as a key mediator explaining how sustainable manufacturing and reverse logistics practices contribute to green supply chain performance in the context of developing countries.